KOMITMEN ANTARA AUDITOR DAN KLIEN: ANTESEDEN DAN KONSEKUENSI - Cahyonowati, Nur (JURNAL AKUNTANSI DAN AUDITING, 2013)
This research examines the antecendents and consequences of commitment in auditor andauditee relationship. Using mail survey to public company and client’s of a local audit firmin Semarang, this research found client orientation is an important determinant for affectivecommitment. Both affective and calculative commitments predicted client’s opportunistic behavior.Affective commitment is suggested to decrease client’s opportunistic behavior, while, calculativecommitment is suggested to increase client’s opportunistic behavior. Finally, this researchsuggested that auditee’s opportunistic behavior determined auditee’s continuance intention.